Integrated marketing communication kopilimana cafe in heightning brand awareness - Najuwa Prischa Alen (Jurnal Scientia, 2024)
Brand awareness is very important for coffee. Because it can increase the interest of business customers. This is similar to what Kopilimana Cafe is doing, which is currently trying to increase brand awareness by using integrated marketing communications, even though sales are decreasing during the pandemic. The purpose of this research is to determine the type of integrated marketing communications that Kopilimana Cafe uses to increase brand awareness. In this research, integrated marketing communication theory is used. This theory includes advertising, sales promotions, events and experiences, public relations and promotions, direct marketing, interactive marketing, and personal selling. This research is qualitative in nature. The research results show that Kopilimana Cafe uses a combination of different marketing strategies: advertising in general media, sales promotion through incongruent variants, events and experiences by collaborating with outside parties, public relations and promotion by collecting information through social media, direct marketing with conveying information about products, individual sales through positive relationships, and interactive marketing through social media.